The Use of English Promotional Videos for Improving Cultural Tours at Tamansari Tourism Village Banyumas - Myradine Hana Saraswati; Artika Wina Fitriani (Jurnal Vokasia, 2024)
This article is entitled Creating English Promotional Videos for Cultural Tours at Tamansari Tourism Village Banyumas. The purpose of this article is to explain the process of making promotional videos in English the obstacles, and solutions in making videos in Tamansari Tourism Village. This tourist attraction was chosen because it is a unique tourist attraction that provides cultural activity tours and has great potential to attract the attention of foreign tourists. In compiling this research, there are three methods, namely observation, interviews, and documentation. In addition, there are three stages in the process of making an English promotional video, namely pre-production, production and post-production. Determining the video concept, making schedules, writing scripts, creating storyboards, conducting briefings with videographers and preparing tools are the preparatory stages known as pre-production. The process of taking video and sound recording is referred to as the production stage. Meanwhile, video editing and video revision is the final stage which is known as post-production. There are many obstacles in the process, but these obstacles can be overcome by several solutions. The resulting video is uploaded on the YouTube channel belonging to Tamansari Tourism Village and aims to assist them in increasing the promotion and visits of foreign and local tourists.